2013
DOI: 10.4103/1357-6283.112803
|View full text |Cite
|
Sign up to set email alerts
|

Leary′s rose to improve negotiation skills among health professionals: Experiences from a Southeast Asian culture

Abstract: Leary's Rose can be used in simulated and authentic work-based educational settings. To train the communication skills of nurses to be the patients' advocates, for example Leary's Rose was used in role plays in which nurses have to negotiate in the patients' interest with the doctor while they have to maintain partnership relationship and avoid opposition with the doctor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…A course to help professionals learn to be patient advocates was piloted for inter-professional participants such as nurses and doctors [ 16 ]. Leary’s Rose, a model to map different hierarchical positions in a negotiation process, was used as an educational tool to help participants face hierarchical encounters [ 17 , 18 ]. The Four-Components Instructional Design model (4C/ID), a model that emphasizes the importance of using whole and authentic learning tasks, was used to design the course [ 16 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…A course to help professionals learn to be patient advocates was piloted for inter-professional participants such as nurses and doctors [ 16 ]. Leary’s Rose, a model to map different hierarchical positions in a negotiation process, was used as an educational tool to help participants face hierarchical encounters [ 17 , 18 ]. The Four-Components Instructional Design model (4C/ID), a model that emphasizes the importance of using whole and authentic learning tasks, was used to design the course [ 16 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…The studies had reported several recommendations for future development of IPE, including a specific suggestion for its development in Asia region [20]. The learning approach also vary to suit the institution condition while keep the IPE implementation as the goal, including improvising the education model to implement the IPE [23]. Implementing IPE in medicine and health sciences institution is a challenge to shift the uniprofessional education to interprofessional education [9].…”
Section: A Link Back Of Ipementioning
confidence: 99%
“…Communication dominated interprofessional work effort in interdisciplinary studies that we found. [30][31][32] The effort to integrate various scientific areas was also seen to care about education in emergency science areas, such as the effort to respond the needs of education in disaster preparedness. 33 It is so interesting where in a hierarchical culture like Indonesia, young researchers are interested to develop areas to erode this hierarchical culture.…”
Section: Area Of Interest In Interprofessional Educationmentioning
confidence: 99%